Synthesis, physical-chemical properties and the study of anti-hypoxemic activity of 5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-thion alkylderivatives - Odyntsova, V. M.; Pruglo, Ye. S.; Одинцова, Віра Миколаївна; Пругло, Євген Сергійович; Одинцова, В. Н.; Пругло, Е. С. (Запорізький державний медичний університет, 2015)
Heterocyclic systems, in particular, 1,2,4-triazole derivatives cause great interest in the development of new medicinal substances for the production of highly effective and safe antihypoxants. This fact has created favorable basis for the synthesis of new alkylderivatives 5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-thion, where R is methyl, phenyl. Aim. In order to identify the most promising active compounds the pharmacological screening of anti-hypoxemic activity of synthesized compounds has been carried out. Results. Due to the results of the study a number of compounds with anti-hypoxemic activity have been revealed. Some regularities between structure and pharmacological effect have been established. Conclusion. This demonstrates the prospects of further studies of the obtained compounds. Значний інтерес у процесі розробки нових лікарських субстанцій для отримання високоефективних і безпечних антигіпоксантів викликають гетероциклічні системи, зокрема похідні 1,2,4-тріазолу. Це створило сприятливе підґрунтя для синтезу нових алкілпохідних 5-(адамантан-1-іл)-4-R-1,2,4-тріазол-3-тіону, де R – метил, феніл. З метою виявлення найбільш активних перспективних сполук здійснили фармакологічний скринінг антигіпоксичної активності речовин, які синтезували. У результаті дослідження виявили ряд сполук, що характеризуються антигіпоксичною дією. Встановили окремі закономірності між структурою та фармакологічним ефектом. Це свідчить про перспективність дослідження отриманих сполук. Большой интерес в разработке новых лекарственных субстанций для получения высокоэффективных и безопасных антигипоксантов вызывают гетероциклические системы, в частности производные 1,2,4-триазола. Это создало благоприятную почву для синтеза новых алкилпроизводных 5-(адамантан-1-ил)-4-R-1,2,4-триазол-3-тиона, где R – метил, фенил. С целью установления наиболее активных перспективных соединений проведен фармакологический скрининг антигипоксической активности синтезированных веществ. В результате исследования установлен ряд соединений, обладающих антигипоксическим действием. Отмечены некоторые закономерности между структурой и фармакологическим эффектом. Это свидетельствует о перспективности дальнейшего исследования полученных соединений.
Синтез, фізико-хімічні властивості та вивчення антигіпоксичної активності алкілпохідних 5-(адамантан-1-іл)-4-R-1,2,4-тріазол-3-тіону
Синтез, физико-химические свойства и изучение антигипоксической активности алкилпроизводных 5-(адамантан-1-ил)-4-R-1,2,4-триазол-3-тиона
Keywords: Derivatives; 1,2,4-triazole; Physical-chemical Properties; Anti-hypoxemic Activity; похідні; 1,2,4-тріазолу; фізико-хімічні властивості; антигіпоксична активність; похідні; 1,2,4-тріазолу; фізико-хімічні властивості; антигіпоксична активність